2013
DOI: 10.3109/02699052.2012.750740
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention for patients at risk for persisting disability after mild traumatic brain injury: A randomized, controlled study

Abstract: An early intervention, offered to patients with an estimated high risk for persisting disability, had no additional effect on symptom level at 3 months after MTBI as compared to TAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…Whether intensified follow-up could help dealing with this uncertainty towards recovery is largely uninvestigated. Two recent papers reported on the effect of an information intervention aimed at high-risk patients (≥three complaints 10 days after injury), in which the authors conclude that the intervention had no effect on activity or participation nor on PTC level after three months [24,25]. Since we found no differences in the average number of complaints between our two groups after two weeks, it might be argued that the identification of at-risk patients based on number of complaints is not appropriate for assessing the need for outpatient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Whether intensified follow-up could help dealing with this uncertainty towards recovery is largely uninvestigated. Two recent papers reported on the effect of an information intervention aimed at high-risk patients (≥three complaints 10 days after injury), in which the authors conclude that the intervention had no effect on activity or participation nor on PTC level after three months [24,25]. Since we found no differences in the average number of complaints between our two groups after two weeks, it might be argued that the identification of at-risk patients based on number of complaints is not appropriate for assessing the need for outpatient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies, our study was adequately powered for evaluation of the secondary outcomes [44]. One strength of our study was that we used sick-leave data from a national register, avoiding high rates of missing outcome data that could bias the results [20,45].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Highlights include a Phase III randomized trial of hypothermia in children, termed the ‘Cool Kids’ study, which recently reported that 48 hours of hypothermia followed by rewarming does not reduce mortality or positively affect recovery from pediatric brain injury (Adelson et al, 2013). An intervention trial randomizing high-risk post-concussion syndrome patients to an early visit to a physician similarly was negative, with similar outcomes to the treatment as the control group (Matuseviciene et al, 2013). Chesnut et al recently reported on their much anticipated trial of continuous invasive ICP monitoring following severe traumatic brain injury, showing no advantage over imaging and clinical examination alone (Chesnut et al, 2012).…”
Section: Pathophysiology Classification and Clinical Management Of Tbimentioning
confidence: 99%